Kajian Yuridis Terhadap Pembatalan Akta Hibah Akibat Penghibah Jatuh Miskin - Jadidyah, Havida; Priyono, Ery Agus (Legal Standing : Jurnal Ilmu Hukum, 2025)
A grant is a form of legal agreement in Indonesian civil law, as regulated in the Civil Code (KUHPerdata). However, in practice, a grant can cause legal problems if there is a change in circumstances on the part of the grantor (grantor), especially if the person concerned experiences economic decline to the point of poverty. This study aims to examine whether the qualifications of the state of poverty experienced by the grantor in the Judicial Review Decision Number: 336/PK/Pdt/2016 are legally appropriate, and to analyze the legal consequences of the cancellation of a deed of gift through a court lawsuit. This study is a normative legal study with a statutory approach and a conceptual approach. The nature of this study is descriptive analysis, with the main data sources in the form of primary and secondary legal materials, which are analyzed qualitatively. The results of the study indicate that Article 1688 paragraph (3) of the Civil Code does open up space for the cancellation of a grant if the grantor falls into poverty, but does not provide a definite measure regarding the limits of "falling into poverty". In the judge's considerations, this assessment is still subjective and is determined based on the judge's belief in the facts presented in court. The legal consequences of the cancellation of a deed of gift are basically a form of legal protection for the grantor who experiences losses or injustice due to the granting of the gift. This study contributes to the development of a normative understanding of legal protection for grantors and the importance of clearer regulations regarding the criteria for falling into poverty in the context of grant cancellation.